(untitled) (Research, Society and Development, 2020)
This work aims to analyze in silico the antiprotozoal potential of Ascaridol. Using the free software PASS online® to evaluate the biological potential of the Ascaridol molecule, where this software provided the values of (Pa) probability of being active and (Pi) probability of being inactive of the compound in different pharmacological characteristics. Ascaridol showed a high probability of being active for the antiprotozoan (Pa= 0,790), Coccidial antiprotozoan (Pa= 0,476) and Leishimania antiprotozoan (Pa= 0,394). Such results corroborate with other studies proving that this compound present in several medicinal plants has great potential as an antiprotozoal agent, being a promising herbal agent.